Untangling Teacher’s Politeness in EFL Classroom: A Case at a Vocational School in Karawang - Kelik Wachyudi; Fauzi Miftakh; Sunarya (ELT in Focus, 2020)
This research at disentangling kinds of polite strategies used by an English teacher in the EFL classroom. This research was based on qualitative approach. The research involved an English teacher at a vocational school in Karawang. The data collection were carried out through the observation of an English teacher in two classroom meetings and were video-recorded. The results showed that the types of polite strategies used by an English teacher included four types of politeness strategies, i.e. positive politeness, negative politeness, bald on-record and off record. As a result, it can be concluded that attention should be given to the language used by the students. This will help the students in developing their English communicative skills as to how to use language relevant to the context.